Production of phenolics via photocatalysis of ball milled lignin–TiO2 mixtures in aqueous suspension. Issue 22 (12th February 2016) - Nair, Vaishakh; Dhar, Piyali; Vinu, R.
Abstract : This work demonstrates the production of value added phenolics and aromatics via UV photocatalysis of lignin–TiO2 mixtures prepared by wet ball milling using different solvents. Abstract : In this study, photocatalytic conversion of lignin to valuable phenolics and aromatic hydrocarbons is demonstrated by subjecting ball milled mixtures of lignin and TiO2 to ultraviolet (UV) radiation. Unlike a majority of the existing studies that reported photocatalytic degradation of lignin that is solubilized in alkaline medium, this study evaluates the decomposition of lignin under natural conditions in aqueous medium. In order to facilitate better contact between lignin and nano-TiO2, the two materials were ball milled in the presence of different media, viz. without solvent, hexane, acetone and water. The ball milled mixtures were characterized using powder XRD, FT-IR and photoluminescence spectroscopy, and scanning electron microscopy. Intimate contact between lignin and TiO2 was achieved using water and acetone as the solvents in wet milling. Photocatalysis experiments were conducted in a batch photoreactor. The aqueous phase products were analyzed using UV-visible spectroscopy, MALDI-TOF and GC mass spectrometry, while the molecular weight of solid lignin was analyzed using GPC. Ball milling resulted in the formation of phenolic compounds even during dark mixing of the mixtures prior to photocatalysis. Ball milled mixtures obtained using acetone and water resulted in a high yield of phenolic compounds after 3–4 hours of UV exposure. At long UV exposure periods, the phenolics production got saturated, possibly due to the deactivation of TiO2 active sites by the intermediates. The main organic compounds produced during photocatalysis include ethyl benzene, acetovanillone, syringaldehyde, acetosyringone, vanillin, 2, 6-dimethoxy benzoquinone and diisobutyl phthalate. Free radical depolymerization reactions of lignin mediated by active hydroxyl and superoxide radicals are responsible for the observed products.